A dynamic simulation model of a continuous horizontal fluidized bed dryer. (6th April 2021) - Gagnon, Francis; Bouchard, Jocelyn; Desbiens, André; Poulin, Éric; Lapointe-Garant, Pierre-Philippe
Highlights: A dynamic model of a continuous horizontal fluidized bed dryer is developed. A screw conveyor control the product residence time in the dryer. The model allows for gas bubbles and product axial mixing. Parameters are lumped and equations are solved at low computational costs. Simulation results are consistent with theory. Abstract: The bottleneck of pharmaceutical continuous wet granulation lines may often be the drying stage. The introduction of horizontal fluidized beds is currently contemplated to solve this issue, inter alia . However, it would require an appropriate process control system to reach and maintain over time the targeted residual moisture of the product. To support the endeavor of both the process and control designs, this paper develops a dynamic model with lumped parameters of a continuous horizontal fluidized bed dryer equipped with a screw conveyor. To this end, the framework makes use of a two-phase tanks-in-series configuration, thus taking into account expected gas bypasses (bubbles) and product axial mixing. Array programming and vectorized operations on each tank reactor allow solving equations explicitly at a low computational cost. Simulation results for calcium carbonate granules in a laboratory scale dryer are consistent with fluidization, drying and continuous reactor fundamentals.